CT-TDMA:efficient TDMA protocol for underwater sensor networks - Lu HONG; Feng HONG; Zheng-bao LI; Zhong-wen GUO (Tongxin xuebao)
Aimed at underwater acoustic sensor networks(UWSN),a novel sender based conflict model with the schemes of allocating continuous time was presented,including local conflict graph(LCG)and a distribute algorithm to generate LCG.Moreover,CT-TDMA,an efficient TDMA protocol based on the conflict model was also proposed,which used heuristic priority rules to allocate transmitting moments for all nodes.CT-TDMA exploits the diversity of propagation delay of different links in UWSN to decrease the idle time between packets at the same receiving node,which helps in improving the throughput.And a heuristic schedule algorithm is applied to shorten the process of allocating continuous time for each node.Simulation results show that,compared with traditional TDMA protocols such as ST-MAC,network throughput of CT-TDMA has increased 20% and end to end delay has decreased 18%;compared to the theoretically optimal scheme with global knowledge,CT-TDMA has achieved 80% network throughput and the end to end delay is only 12% longer.